Anaplasma marginale Infection of Dermacentor andersoni Primary Midgut Cell Culture Is Dependent on Fucosylated Glycans - Vimonish, Rubikah; Capelli-Peixoto, Janaina; Johnson, Wendell C.; Hussein, Hala E.; Taus, Naomi S.; Brayton, Kelly A.; Munderloh, Ulrike G.; Noh, Susan M.; Ueti, Massaro W. (Frontiers in Cellular and Infection Microbiology, 2022)
Tick midgut is the primary infection site required by tick-borne pathogens to initiate their development for transmission. Despite the biological significance of this organ, cell cultures from midgut tissues are unavailable. To study the mechanism of Anaplasma marginale-tick cell interactions, we successfully developed an in vitro Dermacentor andersoni primary midgut cell culture system. Midgut cells were maintained for up to 120 days. We demonstrated the infection of in vitro midgut cells by using an A. marginale omp10::himar1 mutant with continued replication for up to 10 days post-infection. Anaplasma marginale infection of midgut cells regulated the differential expression of tick α-(1,3)-fucosyltransferases A1 and A2. Silencing of α-(1,3)-fucosyltransferase A2 in uninfected midgut cells reduced the display of fucosylated glycans and significantly lowered the susceptibility of midgut cells for A. marginale infection, suggesting that the pathogen utilizes core α-(1,3)-fucose of N-glycans to infect tick midgut cells. This is the first report using in vitro primary D. andersoni midgut cells to study A. marginale-tick cell interactions at the molecular level. The primary midgut cell culture system will further facilitate the investigation of tick-pathogen interactions, leading to the development of novel intervention strategies for tick-borne diseases.